How Stakeholder Pressure and Financial Performance Shape Corporate Sustainability Reporting Transparency - Aditya Septiani; N U Utami (Jurnal Sistem Informasi Bisnis, 2025)
This study examines the impact of stakeholder pressure and financial performance on the transparency of sustainability reporting. We investigate four independent variables: environmentally sensitive industries, investor-oriented industries, consumer-proximity industries, and financial performance. The dependent variable, reporting transparency, is assessed through four factors: reporting frequency, application level, statement level, and assurance. Our sample comprises manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021, selected using purposive sampling. We employ multiple linear regression analysis to evaluate the relationships between variables. The findings reveal that both environmentally sensitive industries and strong financial performance positively influence sustainability reporting transparency. However, we found no significant positive impact from investor-oriented or consumer-proximity industries on reporting transparency. This research contributes to our understanding of the factors driving corporate sustainability disclosure practices in the Indonesian context.